Trypophobia: What Do We Know So Far? A Case Report and Comprehensive Review of the Literature - Martínez-Aguayo, Juan Carlos; Lanfranco, Renzo C.; Arancibia, Marcelo; Sepúlveda, Elisa; Madrid, Eva (Frontiers in Psychiatry, 2018)
In this article, we describe the case of a girl who suffers from a phobia to repetitive patterns, a.k.a. trypophobia. This condition has not yet been recognised by diagnostic taxonomies such as the Diagnostic and Statistical Manual of Mental Disorders (DSM). Trypophobia usually involves an intense and disproportionate fear towards holes, repetitive patterns, protrusions, etc., and in general images that present high-contrast energy at low and midrange spatial frequencies, and it is commonly accompanied by neurovegetative symptoms. In the case we present here, the patient also suffered from generalised anxiety disorder and was treated with sertraline. After she was diagnosed, she showed symptoms of both fear and disgust toward trypophobic images. After some time following the treatment, she only showed disgust toward said images. We finish this case report presenting a comprehensive literature review of the peer-reviewed papers we retrieved after exhaustive search about trypophobia, we discuss what questions this case report contributes to the understanding of this anxiety disorder, and what questions future studies should address in order to achieve a better understanding of trypophobia.